The ion channel TRPV5 regulates B-cell signaling and activation - Mahtani, Trisha; Sheth, Hena; Smith, L. K.; Benedict, Leshawn; Brecier, Aurelie; Ghasemlou, Nader; Treanor, Bebhinn (Frontiers in Immunology, 2024)
Introduction B-cell activation triggers the release of endoplasmic reticulum calcium stores through the store-operated calcium entry (SOCE) pathway resulting in calcium influx by calcium release-activated calcium (CRAC) channels on the plasma membrane. B-cell-specific murine knockouts of SOCE do not impact humoral immunity suggesting that alternative channels may be important. Methods We identified a member of the calcium-permeable transient receptor potential (TRP) ion channel family, TRPV5, as a candidate channel expressed in B cells by a quantitative polymerase chain reaction (qPCR) screen. To further investigate the role of TRPV5 in B-cell responses, we generated a murine TRPV5 knockout (KO) by CRISPR–Cas9. Results We found TRPV5 polarized to B-cell receptor (BCR) clusters upon stimulation in a PI3K–RhoA-dependent manner. TRPV5 KO mice have normal B-cell development and mature B-cell numbers. Surprisingly, calcium influx upon BCR stimulation in primary TRPV5 KO B cells was not impaired; however, differential expression of other calcium-regulating proteins, such as ORAI1, may contribute to a compensatory mechanism for calcium signaling in these cells. We demonstrate that TRPV5 KO B cells have impaired spreading and contraction in response to membrane-bound antigen. Consistent with this, TRPV5 KO B cells have reduced BCR signaling measured through phospho-tyrosine residues. Lastly, we also found that TRPV5 is important for early T-dependent antigen specific responses post-immunization. Discussion Thus, our findings identify a role for TRPV5 in BCR signaling and B-cell activation.